Significant loss of soil inorganic carbon at the continental scale. Issue 2 (2nd July 2021) - Song, Xiao-Dong; Yang, Fei; Wu, Hua-Yong; Zhang, Jing; Li, De-Cheng; Liu, Feng; Zhao, Yu-Guo; Yang, Jin-Ling; Ju, Bing; Cai, Chong-Fa; Huang, Biao; Long, Huai-Yu; et al.
Abstract: Widespread soil acidification due to atmospheric acid deposition and agricultural fertilization may greatly accelerate soil carbonate dissolution and CO2 release. However, to date, few studies have addressed these processes. Here, we use meta-analysis and nationwide-survey datasets to investigate changes in soil inorganic carbon (SIC) stocks in China. We observe an overall decrease in SIC stocks in topsoil (0–30 cm) (11.33 g C m –2 yr –1 ) from the 1980s to the 2010s. Total SIC stocks have decreased by ∼8.99 ± 2.24% (1.37 ± 0.37 Pg C). The average SIC losses across China (0.046 Pg C yr –1 ) and in cropland (0.016 Pg C yr –1 ) account for ∼17.6%–24.0% of the terrestrial C sink and 57.1% of the soil organic carbon sink in cropland, respectively. Nitrogen deposition and climate change have profound influences on SIC cycling. We estimate that ∼19.12%–19.47% of SIC stocks will be further lost by 2100. The consumption of SIC may offset a large portion of global efforts aimed at ecosystem carbon sequestration, which emphasizes the importance of achieving a better understanding of the indirect coupling mechanisms of nitrogen and carbon cycling and of effective countermeasures to minimize SIC loss. Abstract : Significant loss of soil inorganic carbon forced by the input and transformation of anthropogenic reactive nitrogen at the continental scale offsets much of carbon sequestration in the terrestrial ecosystems.